Analysis of the vacuum infusion moulding process - Correia, Nuno André Curado Mateus (2004)
This thesis focuses on flow through compliant porous media with applications to the manufacturing of composites by vacuum infusion (VI). The context of this work is the need for reliability in environmentally friendly composite processing methods for composite materials. Commercial reality and the prospective application to low cost structures for the transportation industry dictate that appropriate emphasis should be put on obtaining robust simulations, ensuring reliability and progressing toward efficient means of process control. In this context, the open mould manufacturing processes which have been used to produce large composite structures, and are not conducive to quality nor environmental responsibility, must be replaced. Hence, establishing composites as a viable alternative requires closed moulding techniques, of which VI is the most practical for large structures, but where reliability is required for economic survival.